2014
DOI: 10.5901/mjss.2014.v5n23p2673
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Impact of Subjective Well-Being on Academic Achievement of Children in District Faisalabad

Abstract: Subjective well-being (SWB) is the form of well-being which focuses on people's feelings

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 26 publications
4
12
0
1
Order By: Relevance
“…According to the study findings, no significant association was detected between gender and positive affect, which is in agreement with some previous findings (Joshanloo & Bakhshi, 2016;Koydemir, 2013). While the results of this study showed a lower subjective well-being among females in comparison with males, the mechanisms leading to gender differences in subjective well-being of migrants are unclear and more empirical research is required to further develop our understanding in this area (Batz-Barbarich et al, 2018;Manzoor et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…According to the study findings, no significant association was detected between gender and positive affect, which is in agreement with some previous findings (Joshanloo & Bakhshi, 2016;Koydemir, 2013). While the results of this study showed a lower subjective well-being among females in comparison with males, the mechanisms leading to gender differences in subjective well-being of migrants are unclear and more empirical research is required to further develop our understanding in this area (Batz-Barbarich et al, 2018;Manzoor et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…First, the significant relationship between happiness and academic performance corroborate previous findings of Mohammadi (2015), Manzoor, Siddique, Riaz, and Riaz (2014) and Tabbodi, Rahgozar, and Abadi (2015). The latter pieces of evidence suggest that happiness may boost academic performance resulting in higher academic performance.…”
Section: Goal Concordance Happiness and Academic Performancesupporting
confidence: 87%
“…The varied findings may have stemmed from the complexity of happiness that is characterized by multiple influential factors (Datu & Valdez, 2012). In some studies, happiness was found to be associated with academic performance (Manzoor, Siddique, Riaz, & Riaz, 2014;Mohammadi, 2015) and academic motivation (Hassanzadeh & Mahdinejad, 2013). Most of the previous studies revealed that happiness increased academic performance, and high academic performance also increases happiness.…”
Section: Happiness and Academic Performancementioning
confidence: 99%
“…In an academic setting, students' emotions shape academic performance (Daniels et al, 2009). Several findings found that happiness was significantly related to students' academic motivation (Hassanzadeh & Mahdinejad, 2013) and academic success (Mohammadi, 2015;Tabbodi, Rahgozar, & Abadi, 2015;Manzoor, Siddique, Riaz, & Riaz, 2014). The impact of happiness can also be found beyond the academic setting.…”
Section: Happiness and Academic Performancementioning
confidence: 99%